Positive Outcomes: Validity, reliability and responsiveness of a novel person‐centred outcome measure for people with HIV. Issue 6 (11th January 2022) - Harding, Richard; Jones, Christopher Iain; Bremner, Stephen; Bristowe, Katherine; West, Brian; Siegert, Richard J.; O'Brien, Kelly K.; Whetham, Jennifer; ,
Abstract: Objectives: Despite successful treatment, people living with HIV experience persisting and burdensome multidimensional problems. We aimed to assess the validity, reliability and responsiveness of Positive Outcomes, a patient‐reported outcome measure for use in clinical practice. Methods: In all, 1392 outpatients in five European countries self‐completed Positive Outcomes, PAM‐13 (patient empowerment), PROQOL‐HIV (quality of life) and FRAIL (frailty) at baseline and 12 months. Analysis assessed: (a) validity (structural, convergent and divergent, discriminant); (b) reliability (internal consistency, test‐retest); and (c) responsiveness. Results: An interpretable four‐factor structure was identified: 'emotional wellbeing', 'interpersonal and sexual wellbeing', 'socioeconomic wellbeing' and 'physical wellbeing'. Moderate to strong convergent validity was found for three subscales of Positive Outcomes and PROQOL ( ρ  = −0.481 to −0.618, all p  < 0.001). Divergent validity was found for total scores with weak ρ (−0.295, p  < 0.001). Discriminant validity was confirmed with worse Positive Outcomes score associated with increasing odds of worse FRAIL group (4.81‐fold, p  < 0.001) and PAM‐13 level (2.28‐fold, p  < 0.001). Internal consistency for total Positive Outcomes and its factors exceeded the conservative α threshold of 0.6. Test‐retest reliability was established: those with stable PAM‐13 and FRAIL scores also reported median Positive Outcomes change of 0. Improved PROQOL‐HIV score baseline to 12 months was associated with improved Positive Outcomes score ( r  = −0.44, p  < 0.001). Conclusions: Positive Outcomes face and content validity was previously established, and the remaining validity, reliability and responsiveness properties are now demonstrated. The items within the brief 22‐item tool are designed to be actionable by health and social care professionals to facilitate the goal of person‐centred care.